Penguatan kelembagaan dan cultural branding Desa Kamal Jember menuju desa wisata sejarah dan budaya berbasis sustainable tourism - Nugraha, Kristian Suhartadi Widi; Paramita, Cempaka; Wulandari, Gusti Ayu; Suryaningsih, Ika Barokah; Destari, Fajar; Ramadina, Novia Amalsya (Universitas Muhammadiyah Mataram, 2024)
Abstrak Program pengabdian masyarakat desa binaan di Desa Kamal Jember merupakan pelaksanaan tahun ke-2 yang bertujuan untuk menguatkan kelembagaan serta identitas budaya atau cultural branding Desa Kamal menuju desa wisata sejarah dan budaya berbasis sustainable tourism. Metode yang digunakan adalah participatory rural appraisal melalui survei, FGD, dan pelatihan intensif (pelatihan pembuatan konten promosi, fotografi lanjutan, hospitality, dan sustainable tourism, serta penyusunan paket wisata). Tim pengabdian mendampingi dalam proses penguatan kelembagaan bagi BUMDES, Pokdarwis, dan perangkat desa serta pembuatan video profil wisata. Hasil dari kegiatan pengabdian ini adalah peningkatan kapasitas dan kompetensi bagi pihak-pihak terkait dalam pengelolaan dan pengembangan wisata Desa Kamal. Cultural branding Desa Kamal menjadi semakin kuat dengan adanya video profil desa yang aktif digunakan sebagai media promosi. Pengelola wisata juga telah memiliki pengetahuan yang baik terkait adopsi dan implementasi sustainable tourism untuk menjaga budaya serta kelestarian alam Desa Kamal. Kata kunci: cultural branding; Desa wisata; sejarah; budaya; sustainable tourism Abstract The second-year community service program in Kamal Village, Jember, is designed to strengthen the organizational management and the village's cultural branding as a historical and cultural tourism destination by implementing sustainable tourism practices. The approach utilized in this initiative includes participatory rural appraisal techniques, such as surveys, focus group discussions (FGDs), and various intensive training sessions. These sessions cover essential topics, including creating promotional content, advanced photography, hospitality, sustainable tourism, and developing tour packages. The community service team has also focused on fortifying local institutions, specifically BUMDES, Pokdarwis, and village officials while producing tourism profile videos. This program aims to enhance the capacity and proficiency of stakeholders involved in managing and developing tourism in Kamal Village. Consequently, the cultural branding of Kamal Village has become significantly more pronounced. The tourism profile videos serve as active promotional tools for Kamal Village. As a result, individuals responsible for tourism within the village now possess an improved understanding of sustainable tourism practices, thereby contributing to maintaining both the natural and cultural sustainability of Kamal Village. Keywords: cultural branding; tourism village; history; culture; sustainable tourism